2020
DOI: 10.1038/s41438-020-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiles reveal that gibberellin-related genes regulate weeping traits in crape myrtle

Abstract: Plant architecture includes vital traits that influence and benefit crops, and economically important trees. Different plant architectures provide natural beauty. Weeping ornamental plants are aesthetically appealing to people. The regulatory mechanism controlling the weeping trait is poorly understood in crape myrtle. To investigate the weeping trait mechanism, transcriptional profiling of different organs in weeping and upright crape myrtle was performed based on phenotype. Phenotypic and histological analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…It has been widely used in studies using A . thaliana , maize, and rice, as well as ornamental plants such as Lagerstroemia [ 34 ] and Lilium ‘Tiny Padhye’ [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used in studies using A . thaliana , maize, and rice, as well as ornamental plants such as Lagerstroemia [ 34 ] and Lilium ‘Tiny Padhye’ [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…used in studies using A. thaliana, maize, and rice, as well as ornamental plants such as Lagerstroemia [34] and Lilium 'Tiny Padhye' [35]. The KEGG database is used to analyze the metabolic pathways and functions of gene products to elucidate the complex biological behaviors of genes.…”
Section: Plos Onementioning
confidence: 99%
“…Plant architectures are signi cantly associated with plant hormones, including gibberellic acid (GA), auxin, and strigolactones (SLs). GA has been thought to promote upward growth and inhibit bending, and it was highly likely to be responsible for the weeping trait [5,6]. Previous researches also suggested that genes associated with auxin and ethylene probably play crucial roles in shoot elongation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many environmental signals, including light and gravity, can in uence plant architecture [5,10]. The branch angle is an important factor in determining plant structure and is regulated by speci c genes.…”
Section: Introductionmentioning
confidence: 99%
“…In peach ( Prunus persica ) an allele was found, appropriately called WEEP, that at least partially is responsible for the trait (Hollender et al 2018). In a totally different species, crape myrtle ( Lagerstroemia ), it was shown that genes involved in the biosynthesis and signaling of the plant hormone gibberellic acid (GA) play a major role in regulating the weeping phenotype (Li et al 2020). GA has been hypothesized to play a role in the weeping phenotype in several species through its involvement in wood formation (reviewed by Hollender and Dardick 2015).…”
mentioning
confidence: 99%